Tantangan Guru Kelas Dalam Melaksanakan Bimbingan dan Konseling Di Sekolah Dasar - Nurlaila, Evi; Rosidah, Ainur; Siregar, Rabiyatul Adawiyah (Paedagogie, 2025)
Teachers play an important role not only as educators, but also as consultants, mediators, and motivators. Skills as teachers directly affect the effectiveness of guidance and counseling which is important for overcoming students' personal, social and academic problems. The implementation of guidance and counseling in elementary schools faces various important challenges that hinder its effectiveness. Understanding the challenges of teachers in implementing guidance and counseling in elementary schools is expected to be anticipated and prepare appropriate solutions. The purpose of the study was to describe the challenges of class teachers in implementing guidance and counseling in elementary schools. The research method used was qualitative descriptive, data collection techniques through interviews, observations and analysis of several articles related to the topic. The subjects of the study involved elementary school teachers in KKG, Purbolinggo District, East Lampung Regency. The results of the study showed that the challenges of class teachers in implementing guidance and counseling in elementary schools arose from various factors, such as role ambiguity, lack of resources, inadequate supervision, and inadequate support from school management. On the other hand, it was stated that there were various factors, including inadequate resources, inadequate training, and lack of cooperation among educators. Addressing these problems is essential to improving the effectiveness of BK services in promoting student development. So that teachers can perform their roles well. The recommendation from this study is the need for ongoing guidance and counseling training for class teachers in elementary schools and increased efforts to raise awareness of their role.